Comparison of Accuracy and Clinical Outcomes of Robot-Assisted Versus Fluoroscopy-Guided Pedicle Screw Placement in Posterior Cervical Surgery. Issue 4 (May 2022) - Su, Xin-Jin; Lv, Zhen-Dong; Chen, Zhi; Wang, Kun; Zhu, Chao; Chen, Hao; Han, Ying-Chao; Song, Qing-Xin; Lao, Li-Feng; Zhang, Yu-Hui; Li, Quan; Shen, Hong-Xing
Study Design: This was a prospective controlled study. Objective: To compare the accuracy and clinical outcomes of robot-assisted (RA) and fluoroscopy-guided (FG) pedicle screw placement in posterior cervical surgery. Methods: This study included 58 patients. The primary outcome measures were the 1-time success rate and the accuracy of pedicle screw placement according to the Gertzbein-Robbins scales. The secondary outcome measures, including the operative time, intraoperative blood loss, hospital stay, cumulative radiation time, radiation dose, intraoperative advent events, and postoperative complications, were recorded and analyzed. The Japanese Orthopedics Association (JOA) scores and Neck Disability Index (NDI) were used to assess the neurological function of patients before and at 3 and 6 months after surgery. Results: The rate of grade A was significantly higher in the RA group than in the FG group (90.6% and 71.1%; P < .001). The clinically acceptable accuracy was 97.2% in the RA group and 90.7% in the FG group ( P = .009). Moreover, the 1-time success rate was significantly higher in the RA group than in the FG group. The RA group had less radiation time ( P < .001) and less radiation dose ( P = .002) but longer operative time ( P = .001). There were no significant differences in terms of intraoperative blood loss, hospital stay, intraoperative adverse events, postoperative complications, JOA scores, and NDI scores at each follow-up time point between the 2 groups. Conclusions: The RA technique achieved higher accuracy and 1-time success rate of pedicle screw placement in posterior cervical surgery while achieving comparable clinical outcomes.